REVIEW ON WORK LIFE BALANCE WHEN WORKING FROM HOME DURING AND AFTER COVID 19 - Fatin Nur Hanis Binti Saharuddin; Nur Darleen Dazeera Binti Azhar; Nur Farhana Binti Ashari; Nashrah Talib; Nurlailatul Qadrina Binti Ahmad Kamal; Amirah Shamimi Binti Mohd Rostum (International Journal of Accounting, Finance and Business, 2022)
Today, with the COVID-19 pandemic hitting the globe today, higher education institutions must shift from the physical classroom to the virtual classroom. Some employees see this as an opportunity for advancement, but others do not because working at WFH is never easy when you have a family. Academics and mothers are seen as carrying a higher load because they must balance work and family. This paper aims at presenting the reviews of the literature on the acceptance of women as academicians and mothers when working from home becomes a future practice. In this research paper, the existing literature on the acceptance of women as academicians and mothers when working from home becomes a future practice in organizations is reviewed. The review will give a holistic understanding of the acceptance of women as academicians and mothers when working from home concept for future researchers and aid to identify the research gap